2015
DOI: 10.1021/acs.jpclett.5b00806
|View full text |Cite
|
Sign up to set email alerts
|

Single Nanoparticle-Based Heteronanojunction as a Plasmon Ruler for Measuring Dielectric Thin Films

Abstract: Nondestructive, noninvasive and accurate measurement of thin film thicknesses on dielectric substrates is challenging. In this work a ruler for measuring thin film thicknesses utilizes the heteronanojunction construct formed between a plasmonic nanoparticle and a high refractive index nonplasmonic substrate. The high near-field sensitivity in the nanojunction renders it suitable for measuring the thickness of intervening dielectric thin films. We demonstrate this by controlling the thickness of dielectric spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…[4] Such NPOM configuration not only serves as ah ighly sensitiveS ERS sensor that permits single-molecule detection [5] and monitoring of interfacial reactions, [6] but also is very useful for metrology applications. [7] Despite these versatile applications, the NPOM-based SERS platform lacks the selectivity that is particularly critical for real sample analysis. The cucurbit[n]urils (CB[n]), af amily of supramolecular hosts with rich host-guest chemistry,h ave been recently employedi nc onstructing selectivem olecular-recognition-based SERS assay.F or example, Mahajan et al [8] reported CB-mediated assembly of AuNPs,i nw hichC Bn ot only functioned as ap recise rigid molecular spacer that produced highly-controllable hot spot nanojunctions, but it also acted as aS ERS reporter for as elf-calibrated in situ SERS sensor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Such NPOM configuration not only serves as ah ighly sensitiveS ERS sensor that permits single-molecule detection [5] and monitoring of interfacial reactions, [6] but also is very useful for metrology applications. [7] Despite these versatile applications, the NPOM-based SERS platform lacks the selectivity that is particularly critical for real sample analysis. The cucurbit[n]urils (CB[n]), af amily of supramolecular hosts with rich host-guest chemistry,h ave been recently employedi nc onstructing selectivem olecular-recognition-based SERS assay.F or example, Mahajan et al [8] reported CB-mediated assembly of AuNPs,i nw hichC Bn ot only functioned as ap recise rigid molecular spacer that produced highly-controllable hot spot nanojunctions, but it also acted as aS ERS reporter for as elf-calibrated in situ SERS sensor.…”
Section: Introductionmentioning
confidence: 99%
“…
The development of highly sensitive and selective methods fort he detection of lead ion (Pb 2 + )i so fg reat scientific importance.I nt his work, we developan ew surfaceenhanced Raman scattering (SERS)-baseds ensor for the selective trace measurement of Pb 2 + .T he SERS-based sensor is assembled from gold nanoparticles (AuNPs)a nd graphene using cucurbit[7]uril( CB[7]) as ap recise molecular glue and al ocal SERS reporter.U pon the addition of Pb 2 + ,C B [7] forms stronger complexes with Pb 2 + and desorbs from AuNPs, resulting in as ensitive "turn-off"o fS ERS signals. This SERS-based assay shows al imit of detection( LOD) of 0.3nm and al inear detection range from 1nm to 0.3 mm for Pb 2 + .
…”
mentioning
confidence: 99%
“…23 In the case of nanoparticle plasmon probes, anion adsorption on single nanoparticle surfaces has been detected through changes in nanoparticle plasmon resonances. 4,5,14 Based on previous work on the role of substrates in the engineering of plasmonic nanoparticles [24][25][26][27] (through interaction of multiple nanoparticles and substrate material) and plasmonic sensing applications, [28][29][30][31] we hypothesize that the optoelectronic and electrochemical properties of the substrate may also play an important role in single-nanoparticle plasmonic electrochemical sensing.…”
mentioning
confidence: 99%
“…AuNPs have unique optical and electronic properties, and therefore have shown great potential as a building block for an extensive range of applications that include diagnostics [98], drug delivery [99], and plasmonics [100][101][102][103]. It is therefore of great interest to create effective DNA recognition layers on the AuNP surface for various applications.…”
Section: Engineering Of Nano-surfaces With Dna Nanostructuresmentioning
confidence: 99%